DI-082 Improvement in the lipid profile of hiv-infected patients after switching to Rilpivirine/Emtricitabine/Tenofovir. (24th March 2015) - Ortonobes Roig, S; De Antonio Cuscó, M; Carballo Martínez, N; Gonzalez Colominas, E; García Paricio, R; Knobel, H; Luque, S
Abstract : Background: Dyslipidaemia has been associated with antiretroviral therapy (ART). Rilpivirine, a new second-generation non-nucleoside reverse transcriptase inhibitor (NNRTI), has a more favourable lipid profile. Purpose: To study the changes in the lipid profile of HIV-infected patients after switching from any ART to rilpivirine/emtricitabine/tenofovir and to assess the efficacy of the switch. Material and methods: Observational study including all patients switching to rilpivirine/emtricitabine/tenofovir from April 2013–2014 in our cohort of 1550 HIV-infected patients. Data: demographics, previous ART, CD4 + count, HIV viral load and lipid parameters at baseline and six months after the switch. All patients were classified as normal baseline or altered lipid profile (NLP or ALP) according to National Cholesterol Education Program cut-offs. Differences between baseline and final values of the lipid parameters were compared between the two groups. Quantitative data were expressed as median (Q1/Q3). Results: 131 patients switched to rilpivirine/emtricitabine/tenofovir: 109 (83.2%) male; age: 43.7 (37.6/50.2) years. Previous ART included 2 nucleoside reverse transcriptase inhibitors (NRTIs) plus: protease inhibitor 46 (35.1%) patients, NNRTI 82 (62.6%) and integrase inhibitor 3 (2.3%). Baseline vs. final: CD4 + count 619 (437/811) vs. 653 (489/830) cell/mcL (p = 0.067) and%patients with HIV-RNA <50 copies/mL: 84.5% vs. 85.7% (p = 0.788). Conclusion: Rilpivirine/emtricitabine/tenofovir improved the lipid profile of HIV-infected patients, while maintaining the immunological and virological efficacy of the ART The reduction in the lipid parameters was significantly higher in patients with altered lipid profile at baseline. References and/or acknowledgements: No conflict of interest.